Embedding Pd‐Cu Alloy Nanoparticles in Shell of Surface‐Porous N‐Doped Carbon Nanosphere for Selective Hydrogenation of p‐Chloronitrobenzene. Issue 10 (10th August 2021) - Liu, Yingcen; Ye, Wanyue; Lin, Hua; Song, Caicheng; Rong, Zeming; Lu, Rongwen; Zhang, Hao; Huang, He; Tang, Zhicheng; Zhang, Shufen
Main observation and conclusion: A catalyst Pd x Cu y /NC in which Pd‐Cu alloy nanoparticles are superficially embeded in shell of surface‐porous N‐doped carbon nanosphere was successfully devised for p ‐chloronitrobenzene ( p ‐CNB) selective hydrogenation. Bimetal ions were loaded in shell of a m ‐phenylenediamine derived core‐shell polymer sphere and the catalyst was obtained after calcination under reducing atmosphere. The as synthesized catalyst exhibited high selectivity in hydrogenation of p ‐CNB to p ‐chloroaniline ( p ‐CAN) (up to 98.8%) under full conversion and the performance was basically remained after 6 cyclic experiments. The reasons for the high selectivity were discussed based on the characterization results of catalyst. The interaction between N‐doped support and metal atoms affected the electron distribution in alloy, electron‐deficient Pd and electron‐rich Cu, and thus improved hydrogenation selectivity. In addition, the alloy nanoparticles were distributed only in the porous shell of support, which benefits to prevent side reactions. This work described a scheme for tactfully designing catalyst for selective hydrogenation, which can provide experience and inspiration for relevant works and fields. Abstract :